DEVELOPMENT OF ARITHMETIC IN EASTERN MATHEMATICIANS AND THEIR WORKS - Orzikulova Gulbahor; Kholmurodov Sardorbek (Social science and innovation, 2023)
In this article, in the history of Central Asia, there were many great figures who combined political wisdom and spiritual courage, religious worldview and encyclopedic knowledge. The works of Muhammad ibn Musa al-Khorazmi, Umar Khayyam, Nasriddin Tusi, Jamshid Giyosiddin al-Koshi, Ulugbek and many other great ancestors have been studied. Their names and their great contributions to the development of world civilization are now known to the whole world. We will get acquainted with their works.